2002
DOI: 10.2135/cropsci2002.1818
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Combining Ability for Ergot Resistance in Grain Sorghum

Abstract: Given the close relationship and similar geographic origin of these species, the possibility of host-plant resis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
4
9
0
1
Order By: Relevance
“…Komolong et al (2003) demonstrated significant differences in ovary colonization rates among three male-sterile sorghum lines after inoculation in a controlled-environment facility by a related ergot fungus C. africana. This corresponds to quantitative differences in resistance among sorghum lines tested under field conditions (Reed et al 2002). Similar results were found in male-sterile wheat infected with C. purpurea (Darlington and Mathre 1976).…”
Section: Introductionsupporting
confidence: 80%
“…Komolong et al (2003) demonstrated significant differences in ovary colonization rates among three male-sterile sorghum lines after inoculation in a controlled-environment facility by a related ergot fungus C. africana. This corresponds to quantitative differences in resistance among sorghum lines tested under field conditions (Reed et al 2002). Similar results were found in male-sterile wheat infected with C. purpurea (Darlington and Mathre 1976).…”
Section: Introductionsupporting
confidence: 80%
“…Initial inoculation or pollination was done at noon. Inoculum consisted of 5 ml of a fresh suspension of macroconidia and secondary conidia adjusted to 1 Â 10 6 conidia ml À1 (Reed et al 2002) obtained from diseased male-sterile plants from a nearby naturally infected field sown 40 d earlier. Pollination of the A-line in the respective treatments was done once with plenty of fresh pollen collected from plants of the maintainer B-line which was grown in border rows.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogen applied in a water suspension of macro and secondary conidia caused a decrease in stigma receptivity; the greatest decrease (40-60 %) occurred when the pollen and the inoculum were deposited Introduction Sorghum ergot (caused by Claviceps africana Frederickson, Mantle & de Milliano) is a disease which in a five-year period (1997)(1998)(1999)(2000)(2001)(2002) has been spread to all the Mexican sorghum (Sorghum bicolor L. Moench) producing areas (Pecina et al 2007), including experimental stations located at 2200 m altitude. Male-sterile genotypes are more sensitive to infection than fertile ones (Meinke & Ryley 1997), and flowering is the vulnerable growth stage (Reed et al 2002). Hence, synchronous flowering among parental lines, deposition time of pollen and conidia on the stigma, and the relative growth rates of pollen tubes and conidia determines whether the ovary will be fertilized by the pollen nuclei or colonized by the fungus (Ryley et al 2002;Mendoza-Onofre et al 2006).…”
mentioning
confidence: 99%
“…Three of 40 Chinese sorghum accessions (Grif627, PI542747, and PI610688) have been evaluated over several growing seasons at the TARS and were included in the study to evaluate ergot response in Texas. IS8525 was included in the evaluation as a resistant control (19) and was obtained from R. G. Henzell (Queensland Department of Primary Industries, Warwick, Australia). IS8525 is a heterogeneous Ethiopian landrace and has two morphological phenotypes based on midrib juiciness, designated as IS8525J (juicy midrib) and IS8525D (dry midrib), and both were included in the study as resistant controls.…”
Section: Chinese Accessions and Ergot Evaluationmentioning
confidence: 99%
“…Ergot resistance sources have been reported by a number of researchers (13,14,18,19,23). Most sources of resistance are not stable across environments and, at present no stable source of resistance is available for sorghum improvement.…”
Section: Introductionmentioning
confidence: 99%